Aerodynamic and aeroelastic characteristics of flexible wind turbine blades under periodic unsteady inflows - Li, Zhanwei; Wen, Binrong; Dong, Xingjian; Peng, Zhike; Qu, Yegao; Zhang, Wenming (Journal of wind engineering and industrial aerodynamics, 2020)
The aeroelastic coupling effect is playing an increasingly important role in the aerodynamic and aeroelastic characteristics of wind turbine blades owing to the increasing size of modern wind turbines. Concurrently, periodic unsteady inflows, including the wind shear (WS), tower shadow (TS), and yawed inflow, further amplify the impacts of aeroelastic coupling. In this study, an aeroelastic model based on the geometrically exact beam theory and blade element momentum method is established. The aeroelastic coupling model is verified based on several previous studies. Taking the NREL 5WM flexible wind turbine blade as an example, the aerodynamic and aeroelastic characteristics under periodic unsteady inflows are investigated. The results show that the WS causes remarkable fluctuations of the flap deflection and yaw moment. The TS effect introduces dramatic changes into the tilt moment, thrust force, and output power when the blade passes by the tower. The yawed inflow leads to a significant reduction in both the output power and thrust force. Compared with other unsteady inflows, the gravity effect on the output power and thrust force are negligible. The response under the combined effect is a summation of the results considering each single influencing factor and is dominated by the major influencing factors. •An aeroelastic coupling model of the wind turbine blade is established.•Flexibility, centrifugal/Coriolis forces, and stress stiffening of the blade are considered.•The aeroelastic model is verified by comparing with previous studies under the steady and unsteady inflows.•Aerodynamic and aeroelastic characteristics of wind turbine blades under different periodic unsteady inflows are studied and compared.